2015
DOI: 10.3390/molecules200916085
|View full text |Cite
|
Sign up to set email alerts
|

N-Monosubstituted Methoxy-oligo(ethylene glycol) Carbamate Ester Prodrugs of Resveratrol

Abstract: Abstract:Resveratrol is a natural polyphenol with many interesting biological activities. Its pharmacological exploitation in vivo is, however, hindered by its rapid elimination via phase II conjugative metabolism at the intestinal and, most importantly, hepatic levels. One approach to bypass this problem relies on prodrugs. We report here the synthesis, characterization, hydrolysis, and in vivo pharmacokinetic behavior of resveratrol prodrugs in which the OH groups are engaged in an N-monosubstituted carbamat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 66 publications
2
15
0
Order By: Relevance
“…The use of methoxy‐OEGs as promoieties was helpful in modulating physicochemical and absorption properties of derivatives . Results of pharmacokinetics studies confirmed the observations already reported for acetal derivatives: variations in the length of the OEG sequence affect the absorption of the prodrug.…”
Section: Strategies To Improve Bioefficacy Of Resveratrolsupporting
confidence: 78%
See 1 more Smart Citation
“…The use of methoxy‐OEGs as promoieties was helpful in modulating physicochemical and absorption properties of derivatives . Results of pharmacokinetics studies confirmed the observations already reported for acetal derivatives: variations in the length of the OEG sequence affect the absorption of the prodrug.…”
Section: Strategies To Improve Bioefficacy Of Resveratrolsupporting
confidence: 78%
“…N ‐monosubstituted carbamate derivatives were thus developed and tested . They are stable in acidic solutions (resembling the gastric pH), but undergo hydrolysis at higher pH values (near‐neutral solutions, resembling the intestinal pH).…”
Section: Strategies To Improve Bioefficacy Of Resveratrolmentioning
confidence: 99%
“…HPLC/ESI-MS analysis was used to confirm the purity (>95%) of isolated intermediates and products. PAP-OH [ 10 ], Ts-MTEG [ 24 ], Ts-MHEG [ 24 ], PAP-1 [ 18 ] and POP-OH [ 49 ], were prepared according to adapted literature procedures. The spectroscopic data for these compounds was consistent with the literature.…”
Section: Methodsmentioning
confidence: 99%
“…Since our active principle is a “small” organic molecule (PAP-1), using relatively short methoxy-oligoethylene glycol (MOEG) chains to modify its properties seems preferable to attaching macromolecules. Our group has previously utilized MOEGs to form prodrugs of the natural polyphenol Resveratrol [ 24 ] endowed with enhanced water solubility and protection from first-pass metabolism after oral administration. The compounds could freely permeate biomembranes, thus suggesting that their psoralenic analogs might as well.…”
Section: Introductionmentioning
confidence: 99%
“…N-Monosubstituted carbamate esters are usually synthesized through two steps: first, the desired primary amine is reacted with a phosgene or its equivalent to give a reactive isocyanate derivative; then, the intermediate is coupled with the phenolic functional group [12,27]. ese procedures, however, provide low yields of the desired trisubstituted resveratrol derivatives likely because the high reactivity of the isocyanate group promotes the polymerization side reaction that entrains the stilbene C-C double bond [28]. e final products were obtained with good yields through this route.…”
Section: Resultsmentioning
confidence: 99%